Effect of Mercury Dose Variation on Growth and Nitrate Reductase Activity in Aquarius palifolius (Nees & Mart.) Christenh. & Byng - Nurhanifah, Tsurayya; Siswanti, Dwi Umi (UI Scholars Hub, 2025)
Mercury, a byproduct of mining, can harm the environment. One method to reduce this impact is through phytoremediation. This study used the Mexican sword (Aquarius palifolius), a plant with the potential to absorb and accumulate mercury. The aim of this study was to examine the effect of mercury stress on nitrate reductase activity, which plays a role in plant productivity, and to assess its impact on growth parameters, including plant height growth rate, leaf length, and number of leaves. Three-month-old A. palifolius plants obtained from rice fields in Sleman were treated with mercury at doses of 0, 14, 16, 18, and 20 ppm. The experiment was conducted in triplicate. Nitrate reductase activity was measured using a spectrophotometer, and growth rate was observed over 15 days. Data were analyzed using One-way analysis of variance (ANOVA) and evaluated using Duncan’s Multiple Range Test (DMRT). Mercury exposure led to adaptations, including a 9.5%–13.5% change in nitrate reductase activity and a 50%–65% reduction in the number of leaves. Growth rates of plant height and number of leaves showed no significant differences, even under mercury stress. These results indicate that A. palifolius can tolerate mercury concentrations of 14–20 ppm and has the potential to functions as a phytoremediation agent.